2008
DOI: 10.1183/09059180.00010905
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal wound healing responses in pulmonary fibrosis: focus on coagulation signalling

Abstract: The normal response of tissue to injury involves a sequence of overlapping events, which need to occur in a timely and controlled manner for successful tissue repair and restoration of normal function. Failure to control the healing process can lead to considerable tissue remodelling and the replacement of functional tissue with permanent fibrous scar tissue.It is proposed that pulmonary fibrosis arises from repetitive, widespread epithelial injury. However, the nature of the insult for the most common and mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
20
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 58 publications
3
20
0
1
Order By: Relevance
“…Possible explanations for our finding include 1) IPF increasing the risk of VTE, and 2) a prothrombotic state leading to the development of IPF and VTE. This study supports the hypothesis that activation of the coagulation cascade may be involved in the pathogenesis of IPF [2,7]. …”
supporting
confidence: 78%
“…Possible explanations for our finding include 1) IPF increasing the risk of VTE, and 2) a prothrombotic state leading to the development of IPF and VTE. This study supports the hypothesis that activation of the coagulation cascade may be involved in the pathogenesis of IPF [2,7]. …”
supporting
confidence: 78%
“…3). PAI-1 is upregulated in late stage SSc-PF and is known to be important in pulmonary fibrosis [7375]. One mechanism by which fibrinolysis may contribute to the resolution of fibrosis is through the induction of fibroblast apoptosis [76].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that PAR-1 is highly expressed on cells implicated in fibrosis in the lungs of people with IPF,32 suggesting the receptor plays an important role in the pathogenic process. Activation of PAR-1 receptors leads to the induction and release of potent profibrotic35 and proinflammatory mediators,5 induces differentiation of fibroblasts to myofibroblasts36 and promotes extracellular matrix protein production 37. Furthermore, active inhibition of the clotting cascade using nebulised heparin, urokinase or activated protein C reduces collagen accumulation and the development of fibrotic lesions in experimental models of lung fibrosis 38 39…”
Section: Discussionmentioning
confidence: 99%